Temperature coefficient of piezoelectric constants in Pb(Mg1/3 Nb2/3)O3 - PbTiO3 ceramics - Manuel Henrique Lente (Materials Research, 2004)
In this work, the thermal stability of piezoelectric constants of PMN-PT ceramics in the tetragonal and rhombohedral phases were investigated in a wide range of temperatures. The results showed that the tetragonal PMN-PT presented higher thermal stability and, consequently, the temperature coefficients for the piezoelectric constants were approximately zero. This result revealed to be much better than that commonly found for PZT ceramics. Although the rhombohedral PMN-PT presented a slight lower thermal stability, the values found for the coupling factor were significantly higher than the tetragonal composition.